Aestheticism in Uttam Nepali’s Abstract Works - Rajbhandari, Jasmine (Journal of Fine Arts Campus, 2022)
The aim of this paper is to explore aesthetic beauty in abstract paintings of Uttam Nepali. The available researches had only found out that he was an abstract painter and painted his feelings and emotions. This article argues that forms and colors he created are for the sake of their beauty. The art forms provide aesthetic pleasure to the viewers. The abstract paintings are analyzed and interpreted in qualitative method. The article focuses that Nepali created the structure of colors and lines by proper arrangements which increases the aesthetic qualities of abstract works and has no any utility purpose. It concludes that the value of Uttam Nepali’s abstract art in the development of Nepali contemporary art is only because of his individual aesthetic form.